2015
DOI: 10.1186/s12906-015-0951-6
|View full text |Cite
|
Sign up to set email alerts
|

Immunological adjuvant effect of the peptide fraction from the larvae of Musca domestica

Abstract: BackgroundThe larvae of Musca domestica (Diptera: Muscidae) have been used traditionally for malnutritional stagnation, decubital necrosis, osteomyelitis, ecthyma and lip scald and also to treat coma and gastric cancer in the traditional Chinese medicine. Its immunomodulatory effects in naïve mice in relation to the traditional uses were also reported. However, the immunological adjuvant potentials of this insect have not yet been studied.MethodsThe peptide fraction from the larvae of Musca domestica L. (MDPF)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 50 publications
1
10
0
Order By: Relevance
“…This study confirms that antigens of LAS are useful for increasing the production of goat livestock antibodies. On the other side Chen et al (2015) used peptide fraction from the larva of Musca domestica as an immunomodulatory. Similarly, Ai et al 2013recorded a high immune-response in mice after using a protein-enriched fraction isolated from larvae of M. domestica.…”
Section: Resultsmentioning
confidence: 99%
“…This study confirms that antigens of LAS are useful for increasing the production of goat livestock antibodies. On the other side Chen et al (2015) used peptide fraction from the larva of Musca domestica as an immunomodulatory. Similarly, Ai et al 2013recorded a high immune-response in mice after using a protein-enriched fraction isolated from larvae of M. domestica.…”
Section: Resultsmentioning
confidence: 99%
“…Many studies have indicated that AMPs from the housefly possess pharmacological value (Cao et al, ; Chen et al, ). Using high‐throughput sequencing methods, seven AMP genes ( CECROPIN, ATTACIN, DEFENSIN, DIPTERICIN, MUSCIN, DOMESTICIN, and LYSOZYME ) have been found in M. domestica infected with a mixture of E. coli and S. aureus (Tang et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have indicated that AMPs from the housefly possess pharmacological value (Cao et al, 2012;Chen et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bioencapsulation of antigens within plant cell wall protects them from degradation from stomach acids/enzymes upon oral delivery; commensal bacterial release enzymes to digest plant cell wall and antigens are then released in the gut lumen (Kwon and Daniell, 2015). Fusion of antigens with GM1 ganglioside receptor-binding protein CTB (cholera non-toxic subunit B) facilitates efficient delivery of vaccine antigens to the immune system (Chen et al, 2015;Gupta et al, 2015;Kumar and Daniell, 2004;Xiao et al, 2016). GM1 is broadly distributed in a variety of cell types including epithelial cells of the gut and antigen-presenting cells, macrophages, dendritic cells, and B cells allowing the fusion antigens to efficiently cross the mucosal barrier via the GM1-ganglioside receptor and provides optimal access to the immune system (Baldauf et al, 2015;Stratmann, 2015).…”
Section: Introductionmentioning
confidence: 99%